Bed time. - Goodhart, Pippa (New York : Franklin Watts, 1997)
Bed time is an enchanting account of a familiar routine at the end of a child's day. While absorbed in the story, your child will be developing important conceptual skills such as an awareness of the passage of time and an understanding of the order of events from beginning to end.
Keywords: Bed time-Fiction; Bed time-Routines